KEBIJAKAN PEMERINTAH DAERAH NUSA TENGGARA BARAT (NTB) DALAM MENGURANGI KETERGANTUNGAN TERHADAP BALI DALAM PENGEMBANGAN PARIWISATA DI LOMBOK - , Lalu Putrawandi Karjaya ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Indonesia existence as state of third world in the reality cannot be discharged from tourism sector. this Sector existence of playing important role in supporting pillar of national economy and since decade 1970-an Bali have come to the especial target of national and international tourism. During more than four Bali decade succeed to predominate the tourism sector in Indonesia. This cause is not expand it other regions in Indonesia which in fact also own the potency which big so. Bali Tourism experience of the crisis after annoying of security of effect of terrorism. At the time of this is a lot of prop regions which follow to become the impact. One of them of Lombok island. For government NTB, existence of Lombok island own the important role in supporting especial inclusion of this province. Others, tourism of Lombok island also personating of interest of people economics, at one blow by seriously lessen the poorness and unemployment. Depending of tourism Lombok island to Bali which big to so make tourism this region become difficult to expand the. Moment happened by the crisis of tourism of effect of security problem Lombok island so. Depending of tourism of Lombok island to Bali later peep out the policy going into effect by fundamentally as existing the solving of problem. This will study exhaustively this thesis research masterpiece.